2017
DOI: 10.1158/1940-6207.capr-17-0050
|View full text |Cite
|
Sign up to set email alerts
|

The Second-Generation PGI2 Analogue Treprostinil Fails to Chemoprevent Tumors in a Murine Lung Adenocarcinoma Model

Abstract: Prostacyclin (prostaglandin I2, PGI2) over-production in FVB/N mice prevents the formation of carcinogen and tobacco smoke induced adenomas, and administration of the oral prostacyclin analog iloprost to wild type mice also prevented carcinogen-induced mouse lung adenoma formation. Former smokers taking oral iloprost showed improved bronchial dysplasia histology compared to placebo. Next generation oral prostacyclin analogues, like treprostinil, were developed for the treatment of pulmonary arterial hypertensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Likewise, administration of a PGI 2 analog, beraprost, reduced tumor metastasis in a mouse lung metastasis model using Lewis lung carcinoma cells (Minami et al, 2015). This contrasts with another study, which showed that a secondgeneration PGI 2 analog, treprostinil, which has potent IP and EP2 affinity, failed to prevent tumors in a mouse lung adenocarcinoma model using JF32 cells (Dwyer-Nield et al, 2017). Despite this, and the known role of EP2 receptor in lung cancer through its activation of the epidermal growth factor (Huang and Chen, 2011), there is no evidence so far that this analog increases the incidence of cancer, including in the lung.…”
Section: Prostaglandin E 2 and Prostacyclin In Lung Cancermentioning
confidence: 70%
“…Likewise, administration of a PGI 2 analog, beraprost, reduced tumor metastasis in a mouse lung metastasis model using Lewis lung carcinoma cells (Minami et al, 2015). This contrasts with another study, which showed that a secondgeneration PGI 2 analog, treprostinil, which has potent IP and EP2 affinity, failed to prevent tumors in a mouse lung adenocarcinoma model using JF32 cells (Dwyer-Nield et al, 2017). Despite this, and the known role of EP2 receptor in lung cancer through its activation of the epidermal growth factor (Huang and Chen, 2011), there is no evidence so far that this analog increases the incidence of cancer, including in the lung.…”
Section: Prostaglandin E 2 and Prostacyclin In Lung Cancermentioning
confidence: 70%
“…Replicate blinded counts were conducted. The Ki67+ nuclei/mm 2 tumor area for each tumor was averaged by group ( Dwyer-Nield et al., 2017 ). H&E stains were done on 5 μm lung sections from urethane, iloprost, and saline groups and were used to confirm adenoma presence and structure.…”
Section: Methodsmentioning
confidence: 99%
“…Replicate blinded counts were conducted. The Ki67+ nuclei/mm 2 lesion area was averaged by group ( Dwyer-Nield et al., 2017 ). A one-way ANOVA with Tukey post-hoc analysis in GraphPad Prism was used to measure significance ( Figure 1 E).…”
Section: Methodsmentioning
confidence: 99%
“…However, the metabolic change leads to further tumor cell growth, aggravation of epithelial–mesenchymal transition (EMT) process, and resistance to treatment. During the treatment of NSCLC, 40% of patients have metastases ( Dwyer-Nield et al, 2017 ), and the main biological process is EMT ( Tulchinsky et al, 2018 ). In the EMT process, cells gradually become spindle-shaped, losing the unique epithelial characteristics, intercellular adhesion, and cytoskeletal structure of epithelial tissue, and possessing polarity, individual migration ability, and invasion ability ( Nieto et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%